2012
DOI: 10.1371/journal.pone.0036780
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of RASSF1A Promoter Methylation in Breast Cancer: A Meta-Analysis of Published Data

Abstract: PurposeEpigenetic alterations have been investigated as prognostic indicators in breast cancer but their translation into clinical practice has been impeded by a lack of appropriate validation. We present the results of a meta-analysis of the associations between RASSF1A promoter methylation status and both disease free survival (DFS) and overall survival (OS) in female breast cancer.MethodsEligible studies were identified through searching the PubMed, Web of Science and Embase databases. Studies were pooled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 26 publications
1
32
0
2
Order By: Relevance
“…Several meta-analysis studies showed an association between RASSF1A promoter hypermethylation and different types of tumors as well as biomarker value of the RASSF1A methylation status (47)(48)(49). This study represents the first meta-analysis of published studies to evaluate the association of RASSF1A promoter hypermethylation with testicular cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Several meta-analysis studies showed an association between RASSF1A promoter hypermethylation and different types of tumors as well as biomarker value of the RASSF1A methylation status (47)(48)(49). This study represents the first meta-analysis of published studies to evaluate the association of RASSF1A promoter hypermethylation with testicular cancer.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that the CpG methylation of RASSF1A promoter can lead to the loss-of-expression of RASSF1A 14. Previous studies have found that the RASSF1A promoter methylation can increase the risk of lung cancer, breast cancer, prostate cancer, ovarian cancer, renal cell carcinoma, colorectal cancer, hepatocellular carcinoma, and gastric cancer 1724. Furthermore, these results indicated that the RASSF1A promoter methylation may be a significant prognostic factor for many human cancers.…”
Section: Introductionmentioning
confidence: 82%
“…Of these genes Cyclin D2 exhibited a stark contrast in frequency between AAs (64%) and Caucasians (19%). While some of these genes may not be linked to prognosis, hypermethylation of Cyclin D2 and RASSF1A are both associated with higher relapse rates and poor overall survival (91)(92)(93).…”
Section: Insights From Other Cancersmentioning
confidence: 99%